HUKUM DAN PELAKU INVESTASI DALAM PERBANKAN - Y. Teguh Handaruprasetyo (Faculty of Law, Universitas Diponegoro, 2011)
Investment agents within banking sector if could be said with capitalist, when have the power of share more than 50% there was tendency to used their power to influences bank operational and carried out abused of power therefore this matter usually made bank became not healthy and finally closed by big power within such bank investment that oftentimes carried out bank fund deviation, therefore to anticipate it was by limiting ownership within banking. Review within banking regulation concept existed also carried out is there already adjust by condition recently. Is it still relevant within Bl banking paradigm as the leader of the last resort after absence new institutions such Loan Guarantor Institution, Financial Service Superintend ant Organization and others. Note that the lender of the last resort was only to assist broken bank that could bother economy systematically, whereas recently already exist guarantor institution for client protection and next already exist own superintendent insUtution. According to the writer need absence paradigm alteration were eliminating function the lender of the last resort within Bank Indonesia.